Penerapan Media Audiovisual untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran PAI Materi Asmaul Husna Kelas IV SDN 14 Bahagia Padang Gelugur - Yanti, Asmida Nasdi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) among fourth-grade students at SDN 14 Bahagia Padang Gelugur using the Classroom Action Research (CAR) approach based on Kurt Lewin’s model. The study consisted of two cycles, each involving planning, action, observation, and reflection stages. In Cycle I, student learning outcomes reached an average of 54.54%, failing to meet the success criteria. Analysis revealed a lack of motivation and limited use of learning media. In Cycle II, strategies were improved by optimizing audio-visual media and interactive teaching methods, resulting in an increased average score of 72.53%. These findings align with the theories of constructivism, multimedia learning, and the Zone of Proximal Development (ZPD), emphasizing active learning, innovative media, and teacher guidance. The study concludes that the CAR approach effectively enhances students’ learning outcomes and engagement. These findings provide practical guidance for teachers in designing more interactive and meaningful learning experiences.